2015
DOI: 10.1007/s00431-015-2627-0
|View full text |Cite
|
Sign up to set email alerts
|

Constipation, renovascular hypertension, and posterior reversible encephalopathy syndrome (PRES)

Abstract: Severe functional constipation is a previously unrecognized cause of severe acute hypertension, resulting in life-threatening neurologic dysfunction. We highlight this unrecognized complication of severe functional constipation with fecal impaction that is potentially preventable if managed appropriately.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…First, prebiotic lactulose can regulate the gut microbiotas of people who consume HSDs, thus improving the intestinal microenvironments and alleviating hypertensive symptoms. Second, individuals who consume HSDs will have hypertension and constipation . Linz et al .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, prebiotic lactulose can regulate the gut microbiotas of people who consume HSDs, thus improving the intestinal microenvironments and alleviating hypertensive symptoms. Second, individuals who consume HSDs will have hypertension and constipation . Linz et al .…”
Section: Introductionmentioning
confidence: 99%
“…Second, individuals who consume HSDs will have hypertension and constipation. [13] Linz et al [12] reported that treating constipation was a useful strategy for reducing hypertension caused by HSD consumption; thus, lactulose, as a feasible mild deobstruent, can alleviate hypertension. Third, fructo-oligosaccharides and long-chain inulin improve lipid metabolism in hypertensive patients and glucose (GLU) metabolism in mice, thus lowering the host's blood pressure.…”
Section: Introductionmentioning
confidence: 99%
“…Hypothyroid patients faced more constipation problems than hyperthyroid, and this problem of constipation is associated with gender and age. Female patients were more at risk of constipation than the male [27]. Hyperthyroid patients were more at risk of irregularities in the sleep cycle than in the hypothyroid cases whereas difficulties in breathing were equally distributed between both types of thyroid disorder but more among women.…”
Section: Discussionmentioning
confidence: 88%
“…However, in this case, the encephalopathy was probably due to a secondary renovascular hypertension and not only to the constipation itself. 10 On the other hand, it has been reported that elevated intracranial pressure can influence gut motility. 3 Increases in intracranial pressure induce massive increases in sympathetic activity, which can be responsible for many of the gastrointestinal symptoms that patients display, such as hypersecretion of gastric acid and gastric hypomotility.…”
Section: Discussionmentioning
confidence: 99%